Influence of winter water temperatures on the physiological state of carp (Cyprinus carpio) - Tsurkan , L. V. (Regulatory Mechanisms in Biosystems, 2022)
In the winter period, water temperature is one of the main factors influencing the physiological state of fish. Its optimal and stable indicator during the whole winter period guarantees high yield of fish and its quality. To this date, the winter period is characterized by elevated temperatures with acute fluctuations. In this work, the main object of study is carp (Cyprinus carpio) at the age of six (young-of-the-year) and ten (one-year) months. The aim of this study was to determine how much the period of the optimal winter water temperatures decreased and how this affected the weight and fatness, hematological profiles, erythrocyte indices and basic biochemical parameters of carp muscle tissue. As a result of research, it was found that optimal winter water temperatures decreased by an average of two months, which affected the physiological state of carp. Consequently, there was a decrease in body weight and fatness. Dissolved oxygen level, pH, nitrites, nitrates and hardness were normal, while oxidation was increased. Muscle fat and protein levels decreased to critical levels, at the same time, moisture and ash levels were noted to increase. The total content of red blood cells decreased, however, the level of hemoglobin, mean corpuscular hemoglobin (MCH), mean cell hemoglobin concentration (MCHC) increased. With increasing hemoglobin content and concentration, mean corpuscular volume (MCV) decreased. After wintering, the number of white blood cells increased. The biochemical profile of carp blood showed a decrease in total protein in blood serum, albumin, triglycerides, cholesterol and glucose. After wintering, there was an increase in creatinine, phosphorus and calcium. Knowing how much the period of optimal winter temperatures has shortened, and how this affects the state of carp at the physiological level, will provide an opportunity to develop recommendations for improving wintering technologies. Considering the dynamics of climate change, the research in this area is promising.